Pengembangan Sistem Penjualan Toko Mebel berbasis Web (Studi Kasus : Karunia Jaya Damean Mebel Singosari) - Agasi Putra Septiyanto; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Karunia Jaya Damean Furniture store is a business running in the sale of home supplies/furniture located in Singosari, Malang Regency. All furniture items sold at the Karunia Jaya Damean Furniture store are made of wood. The problem at Karunia Jaya Damean Furniture store is weak sales strategy. The sales strategy administered by this store is traditional, where the information about sales of goods is shared from one person to another. Other than the sales strategy, the process of ordering furniture at the store is still traditional, is order are handled through by telephone communication media or direct visits to the store. This can be a problem for the customers who want to order according to their wishes, but they are outside of another city or region, so it's impossible to visit the store directly. The web-based furniture store sales system is developed to overcome the problems found in the Karunia Jaya Damean Furniture store. The development of the system uses the waterfall model with an Object-Oriented approach. The developed system using the PHP programming language with the CodeIgniter framework. The system has been success examined by unit testing, integration testing and validation testing with the results of all tests are valid.